Decreased capacity for mental effort after single supratentorial lacunar infarct may affect performance in everyday life. Issue 5 (1st November 1998) - Van Zandvoort, M J E; Kappelle, L J; Algra, A; De Haan, E H F
Abstract : OBJECTIVES: The long term outcome after a single symptomatic lacunar infarct may be less favourable than is generally assumed. Patients often present with complaints such as fatigue or "being different from before the stroke", for which there are no obvious physical explanations. Although cognitive functioning is considered normal in most patients with lacunar infarction in the internal capsule or corona radiata, a study was carried out to determine if subclinical changes in mental or emotional function can explain these vague complaints characteristic for their disablement. METHODS: Sixteen patients, each with a single symptomatic supratentorial lacunar infarct, and 16 matched healthy controls were examined with an extensive neuropsychological screening battery and a standardised questionnaire aimed at emotional problems. The mean number of correct responses was calculated for each subject and averaged within each group. RESULTS: Although, on the whole, there were no differences in performance, patients' results on the following tasks in different modalities showed evidence for decreased performance under relatively more demanding conditions: line orientation task (mean difference (MD) 261 ms; 95% confidence interval (95%CI) 94 to 428), Rey-Osterrieth delayed recall (MD−3.8, 95% CI −7.5 to 0.0), visual elevator subtest of the everyday attention task (EAT) (MD −0.7, 95% CI −1.5 to 0.1), lottery subtest of the EAT (MD −0.6, 95% CI −1.3 to 0.1) and WAIS similarities (MD −3.2 95% CI −6.3 to 0.1). Patients also more often had emotional disturbances than controls. CONCLUSION: Both subtle cognitive impairments and emotional disturbances may play a part in the decreased competence in everyday life of patients with a supratentorial lacunar infarct.